Legal Certainty and Protection of Indigenous Peoples' Land Rights Ownership on Land from Coastal Reclamation Based on Indonesian Positive Law (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This research aims to analyze the issue of legal certainty and the protection of indigenous peoples' land rights and ownership of reclaimed coastal land in Indonesia's positive legal system. Although the 1945 Constitution and the Basic Agrarian Law (UUPA) have recognized the existence of indigenous peoples and their customary rights, legal reality shows that reclaimed land is often not included in the recognition area. Coastal reclamation carried out by the state or corporations usually ignores the participation of indigenous peoples, resulting in agrarian conflicts and legal uncertainty. Through a normative juridical approach and the concepts of legal certainty theory and legal protection theory, this research concludes that participatory and fair policy reformulation and administrative mechanisms are needed, so that the rights of indigenous peoples are not marginalized in the process of coastal development, especially in coastal reclamation.